Antimicrobial Activity of Newly Synthesized Thiabendazoles - Siddappa A. Patil; Vikrant Patil; Renukadevi Patil; Alejandro Bugarin; Shivaputra A. Patil (Current Advances in Chemistry and Biochemistry Vol. 2, 2021)
In the present work, three new thiabendazole derivatives (4b and 6a-c) and their intermediates (3a-b) were synthesised by the reaction of inexpensive easily available amines with 4-cyanothiazole in moderate to good yields. The preliminary in vitro antimicrobial evaluation was conducted for all the compounds (3a-b, 4b and 6a-c) by the whole cell growth inhibition assays method towards Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, Acinetobacter baumannii, Pseudomonas aeruginosa, Candida albicans and Cryptococcus neoformansvar. Our research efforts identified the highly potent antibacterial agent 3b which displayed strong growth inhibition (77.12%) towards gram-negative bacteria Acinetobacter baumannii.